Municipal responses to HIV and AIDS: a case study of uMgungundlovu district and four of its local municipalities in KwaZulu-Natal - Makhathini, Thandeka (My University, 2010)
ABSTRACT The study examined the nature of municipal responses to HIV and AIDS in uMgungundlovu District and its four local municipalities. The study assessed the responses through an investigation of HIV and AIDS interventions as perceived by people living with HIV and AIDS and leaders of Community Based Organisations. The study also examined how HIV and AIDS are taken into account in the Integrated Development Plan (IDP) process and to evaluate whether people living with HIV and AIDS and Community Based Organisations are invited to participate in the IDP process. The other objective was to assess the capacity and support municipalities had in order to respond to the epidemic. The study employed a qualitative method of enquiry. Primary and secondary sources were utilised and they included, in-depth interviews with municipal officials, focus group discussions with people living with HIV and AIDS and Community Based Organisation leaders. The study also included the analysis of the following documents: IDP’s documents, HIV and AIDS Strategic Plans and Policies and projects reports of the five municipalities. The study found that the municipal response to HIV and AIDS varied across municipalities however all the five municipalities experienced similar challenges. The study also found that the municipal response is hampered by human and financial resource constraints and the limited political will from political leaders and senior managers. The study identified that municipalities have begun to understand that HIV and AIDS are issues that require a range of interventions from local government. This is evident because municipalities have developed and implemented HIV and AIDS Strategic Plans, Policies and HIV and AIDS workplace programmes. The study found that municipalities have initiated various interventions but they are almost health focused. These include HIV and AIDS awareness activities, VCT, home based care and condom distribution. This health focused response illustrates that most municipalities are struggling to respond developmentally. The study concludes with key findings leading to a range of recommendations. However there are good practices of HIV and AIDS mainstreaming in uMngeni and Msunduzi municipalities. It is important that municipalities mainstream HIV and AIDS into the core mandate of local government. They can do this by integrating HIV and AIDS into all the phases of the Integrated Development Plan and in all programmes, policies, and projects of the municipality. Political commitment from political leadership is a critical element of an effective response as they can play a critical role in driving the HIV and AIDS strategy and in mobilising local resources as well as impacting on behaviours. Given the range of non-medical drivers of the HIV epidemic, as well as impacts of infection, illness and death in households and communities, the fight against HIV and AIDS won’t be successful outside multi-sectoral partnerships. It is important that for municipalities to develop solid, collaborative partnerships with stakeholders from all tiers of government, the private sector and with civil society groups. It is also critical for municipalities to engage civil society groups because they are the ones who work with people infected and affected by HIV and AIDS. This will enable municipalities to understand the local situation of the epidemic and planning will be informed by local realities.